Reaching into the Past for Future Resilience: Recovery Efforts in Maine Rivers and Coastal Waters - Lichter, John; Ames, Ted (Maine Policy Review, 2012)
John Lichter and Ted Ames discuss how analysis of environmental histories of human activities affecting Maine’s estuary, river, and coastal marine ecosystems can shed light on the role key fish species may play. Through Maine’s Sustainability Solutions Initiative, a group of researchers from Bowdoin, Bates, University of Southern Maine, and Penobscot East Resource Center have teamed up to examine ecological recovery in the state’s waterways and coastal fisheries. Several river restoration efforts were already underway, and others are being planned as a direct result of this interdisciplinary project.
Keywords: Maine; environmental history; river restoration; coastal restoration